Does physiological-based cord clamping improve cerebral tissue oxygenation and perfusion in healthy term neonates? – A randomized controlled trial - Schwaberger, Bernhard; Ribitsch, Mirjam; Pichler, Gerhard; Krainer, Marlies; Avian, Alexander; Baik-Schneditz, Nariae; Ziehenberger, Evelyn; Mileder, Lukas Peter; Martensen, Johann; Mattersberger, Christian; Wolfsberger, Christina Helene; Urlesberger, Berndt (Frontiers in Pediatrics, 2023)
Objectives: To evaluate cerebral tissue oxygenation index (cTOI) during neonatal transition in healthy term neonates receiving either physiological-based cord clamping (PBCC) or early cord clamping (ECC). Secondary aim was to evaluate changes in cerebral blood volume (∆CBV), peripheral arterial oxygen saturation (SpO2) and heart rate (HR) in those neonates. Materials and Methods: We conducted a randomized controlled trial (clinicaltrials.gov: NCT02763436) including vaginally delivered healthy term neonates. Continuous measurements of cTOI and ∆CBV using near-infrared spectroscopy, and of SpO2 and HR using pulse oximetry were performed within the first 15 minutes after birth. Data of each minute of the PBCC group (cord clamping [CC] after the onset of stable regular breathing) were compared to those of the ECC group (CC <1 minute after birth). Results: A total of 71 term neonates (PBCC: n = 35, ECC: n = 36) with a mean (SD) gestational age of 40.0 (1.0) weeks and a birth weight of 3479 (424) grams were included. Median (IQR) time of CC was 275 (197-345) seconds and 58 (35-86) seconds in the PBCC and ECC group, respectively (p < 0.001). There were no significant differences between the two groups regarding cTOI (p = 0.319), ∆CBV (p = 0.814), SpO2 (p = 0.322) and HR (p = 0.878) during the first 15 minutes after birth. Conclusion: There were no significant differences in the course of cTOI as well as ΔCBV, SpO2 and HR during the first 15 minutes after birth in healthy term neonates, who received either CC after the onset of stable regular breathing or ECC < 1 minute. Thus, deferring CC ≥ 1 minute following a physiological-based approach offers no benefits regarding cerebral tissue oxygenation and perfusion after uncomplicated vaginal delivery compared to a time-based ECC approach.